Trunk music - Connelly, Michael (London : Orion, 1997)
A detective investigating a murder is fired for his efforts because his probe disrupted an FBI sting operation. He is Hieronymous "Harry" Bosch of the Los Angeles Police Department who was investigating the slaying of a movie producer. A tale of Hollywood films, crooked money and crooked cops. By the author of The Last Coyote.
National College of Business and Arts
Keywords: Police -- Fiction; Detective and mystery fiction